The Mediating Role of Supply Chain Integration on the Relationship among Learning, Agility and on Firm Performance: Evidence from Indonesia - Endah Budiarti; Sutrisno Sutrisno; Abd Kadir; Tri Andjarwati; Muhammad Yasin (International Journal of Supply Chain Management, 2020)
The investigation aims to identify the association in learning, agility, organization’s performance and supply chain. Data for the research was collected from Indonesia and is comprised of 350 public limited companies registered in Indonesian Stock Exchange (ISE). The results reveal that learning either it is internal or external is influenced significantly by the supply chain integration. Moreover, organizational performance and agility were not influenced by supply chain integration. While internal learning has not influenced agility but influenced firm performance. On the other hand, external learning has influenced organizational performance that is not statistically significant.